2005
DOI: 10.1007/s10549-005-9118-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity and race on prognosis in lymph node-negative, estrogen receptor-negative breast cancer

Abstract: For women with node-negative, ER-breast cancer from clinical trials, obesity did not increase recurrence risk, but was associated with greater risk for second cancers, CBC, and mortality, particularly non-breast cancer deaths. Less favorable prognosis for black women persists in clinical trials, and is in part attributable to non-breast cancer outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
86
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 48 publications
7
86
1
6
Order By: Relevance
“…Estudos têm demonstrado a existência de associação entre fatores étnicos/raciais e a sobrevida pela doença, sendo a raça negra, em geral, considerada como fator de pior prognóstico 14,15,16 , o que pode, em parte, estar relacionado ao nível sócio-econômico. Nesta pesquisa, embora tenha sido observada sobrevida inferior nas pacientes não brancas na análise não ajustada, a cor da pele não se mostrou, no modelo multivariado, estatisticamente associada ao risco de óbito.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estudos têm demonstrado a existência de associação entre fatores étnicos/raciais e a sobrevida pela doença, sendo a raça negra, em geral, considerada como fator de pior prognóstico 14,15,16 , o que pode, em parte, estar relacionado ao nível sócio-econômico. Nesta pesquisa, embora tenha sido observada sobrevida inferior nas pacientes não brancas na análise não ajustada, a cor da pele não se mostrou, no modelo multivariado, estatisticamente associada ao risco de óbito.…”
Section: Discussionunclassified
“…Nos Estados Unidos, tem sido evidenciada pior sobrevida nas mulheres negras e de outros grupos étnicos em comparação com as mulheres brancas caucasianas 14,15,16 , o que pode resultar de desigualdades no acesso e na qualidade de cuidados à saúde e/ou de diferenças nas características tumorais dentro de cada estádio. Inegavelmente, está-dios mais precoces se associam à sobrevida e ao tempo livre de doença mais elevados 4,16,17,18 .…”
unclassified
“…One of the largest study with ER-and lymph node-negative breast cancer patients was the NSABP-14 trial [9], and confirmed that the risk of contralateral breast cancer and overall mortality (although not necessarily breast cancer-related mortality) were increased in the obese patients. In addition, the subgroup analysis of the BIG 02-98 trial also showed that obese patients appeared to have worse outcomes if they had at least 1 hormone receptor negativity [5].…”
Section: Discussionmentioning
confidence: 78%
“…Although obesity and lack of hormone receptors are known as distinctive unfavorable prognostic factors in breast cancer, there are only limited data on how obesity interacts with prognosis of non-luminal tumors [8,9]. TNBC is an aggressive subtype of breast cancer with higher local and distant recurrence rates and shorter survival, and, in this study, we evaluated the impact of obesity on clinical outcomes of patients with this form of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Dignam et al (2006) demonstrated higher BMI to be associated with greater overall mortality within a hormone-insensitive, node-negative breast cancer patient population. This was most pronounced in patients with a BMI >35, who were noted to have a two-fold increased risk of non-cancer death, most commonly due to chronic disease.…”
Section: Discussionmentioning
confidence: 92%